Higher Education in Costa Rica: Ranking and decolonization? - D’ Antoni, Maurizia (2013)
This essay contrasts the decolonization proposal of the being and of knowledge with the imaginary in the public university and in “the quality assurance policies”, its purposes, and relation to production methods. The author states that developing distrust towards all forms of colonization of knowledge represent a “quality improvement” in higher education. The main findings refer to the need of discussing the risks within the “improvement” and homogenization processes in higher education having, as a relevant and inherent aspect, an epistemological detachment task as a decolonization key from the public university in Costa Rica.